ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANI JAGUNG DI KABUPATEN KARO - Nasution, Siti Khadijah Hidayati; Rahmanta, Rahmanta; Jufri, M. (Fakultas Pertanian, Universitas Janabadra, 2024)
Corn is one of the leading commodities in Karo Regency, North Sumatra Province, used as a substitute for rice and as a raw material for animal feed which is able to penetrate the international market. One of the corn production centers in Karo Regency is located in Tigabinanga, Laubaleng and Mardingding Districts with the majority of farmers cultivating corn as their main livelihood. The aim of this research is to analyze the cost structure, revenue, income and feasibility of corn farming. Data collection techniques through observation and interviews using questionnaires. Sampling of farmers was carried out using a simple random sampling method of 45 people. The data analysis model uses cost structure analysis, revenue, income and calculation of the feasibility of corn farming with the R/C ratio. The research results show that corn farming in Karo Regency is profitable with an average income of respondents of IDR 15261695/MT from total costs of IDR 32,672,740/MT. Feasibility analysis shows the B/C ratio value is 1.47 so that corn farming is feasible.Keywords: feasibility analysis, costs, income, corn farming INTISARIJagung merupakan salah satu komoditi unggulan di Kabupaten Karo Provinsi Sumatera Utara digunakan sebagai bahan pengganti padi dan bahan baku pakan ternak yang mampu menembus pasar internasional. Salah satu sentra produksi jagung di Kabupaten Karo ini terletak di Kecamatan Tigabinanga, Laubaleng dan Mardingding dengan mayoritas petani mengusahakan komoditi jagung sebagai mata pencaharian utama. Tujuan penelitian ini untuk menganalisis struktur biaya, penerimaan, pendapatan dan kelayakan usahatani jagung. Teknik pengumpulan data melalui observasi dan wawancara menggunakan kuesioner. Pengambilan sampel petani dilakukan dengan metode simple random sampling sebanyak 45 orang. Model analisis data menggunakan analisis struktur biaya, penerimaan, pendapatan dan perhitungan kelayakan usahatani jagung dengan R/C ratio. Hasil penelitian menunjukkan usahatani jagung di Kabupaten Karo menguntungkan dengan rata-rata pendapatan responden sebesar Rp 15261695/MT dari total biaya sebesar Rp 32.672.740/MT. Analisis kelayakan menunjukkan nilai B/C ratio sebesar 1,47 sehingga usahatani jagung layak diusahakan.Kata kunci: analisis kelayakan, biaya, pendapatan, usahatani jagung,